Perceived behavioural control as a key enabler of sustainable behaviour among university students: Evidence from Malaysian public universities - Hassan, Norhasliza (Journal of Islamic, Social, Economics and Development, 2025)
Despite increasing sustainability awareness and extensive educational initiatives, university students’ engagement in sustainable behaviour remains inconsistent. Prior studies grounded in the Theory of Planned Behaviour (TPB) have largely focused on attitudinal and normative determinants of behaviour, with limited emphasis on individuals’ perceived capacity to act sustainably. Addressing this gap, the present study examines perceived behavioural control (PBC) as a key enabler of sustainable behaviour among students of Malaysian public universities. Using a quantitative cross-sectional design, data were collected from 956 students and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that perceived behavioural control has a significant and strong positive effect on sustainable behaviour, suggesting that students are more likely to engage in sustainable practices when they perceive sufficient capability and institutional support. The study extends the application of TPB by foregrounding capacity-based explanations of sustainable behaviour and provides practical insights for higher education sustainability initiatives.